2020
DOI: 10.3748/wjg.v26.i39.5983
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in ulcerative colitis and verification in a colitis mouse model by bioinformatics analyses

Abstract: BACKGROUND Ulcerative colitis (UC) is an inflammatory bowel disease that is difficult to diagnose and treat. To date, the degree of inflammation in patients with UC has mainly been determined by measuring the levels of nonspecific indicators, such as C-reactive protein and the erythrocyte sedimentation rate, but these indicators have an unsatisfactory specificity. In this study, we performed bioinformatics analysis using data from the National Center for Biotechnology Information-Gene Expression O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…This assumption was confirmed by comparing our results to intestinal transcriptomic profiles of UC patients, supporting the rational to use ENS primary cultures to study chemokines activation under inflammatory stress. Most particularly, these results support the involvement of broad chemokine pathways in the inflammatory active phases of IBD and are in line with recent data of the literature based on the analysis of additional publicly available genome-wide data-sets of UC patients [39]. In support of this data, expression of Cxcl1 [9] and Cxcl2 [40,41] has also been shown to be increased in intestinal mucosal biopsies of IBD patients in additional independent studies.…”
Section: Discussionsupporting
confidence: 90%
“…This assumption was confirmed by comparing our results to intestinal transcriptomic profiles of UC patients, supporting the rational to use ENS primary cultures to study chemokines activation under inflammatory stress. Most particularly, these results support the involvement of broad chemokine pathways in the inflammatory active phases of IBD and are in line with recent data of the literature based on the analysis of additional publicly available genome-wide data-sets of UC patients [39]. In support of this data, expression of Cxcl1 [9] and Cxcl2 [40,41] has also been shown to be increased in intestinal mucosal biopsies of IBD patients in additional independent studies.…”
Section: Discussionsupporting
confidence: 90%
“…However, differences in measurement platforms, lab protocols, sample sizes, and operators render gene expression levels incomparable. In recent years, several studies based on microarray technology have been published to identify effective biomarkers in UC, most of which are prone to utilizing intersecting genes from different microarrays to perform analyses (Cheng et al, 2019(Cheng et al, , 2020Shi et al, 2020;Cao et al, 2021). As shown in Table 3, these methods can be applied to fewer datasets (≤3 datasets) because more datasets represent overly strict inclusion criteria, leading to fewer DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the six hub genes was confirmed in the DSS-induced UC mouse model. In published studies, some scholars screened diagnostic biomarkers for UC from the DEGs identified from a single dataset or an overlap of two or three datasets via bioinformatics analyses (Cheng et al, 2019(Cheng et al, , 2020Shi et al, 2020;Cao et al, 2021). In contrast, the advantage of this research lies in the larger dataset obtained by combining data from six GEO datasets, which increased the sample size and ensured the stability and relative reliability of the conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Symptoms of UC usually present with bloody mucopurulent stool, diarrhea, and bellyache, and they seriously impair the level of health for patients. [ 2 ] In addition, diagnosis of UC mainly relies on endoscopy and clinical symptoms. [ 3 ] It has been reported that the occurrence rate of UC is increasing globally.…”
Section: Introductionmentioning
confidence: 99%